A Year in the Life of a Third Space Urban Teacher Residency Using Inquiry to Reinvent Teacher Education - Taylor, Monica; Klein, Emily J.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2015)
This book weaves together voices of faculty, residents, mentors, administrators, community organizers, and students who have lived together in a third space urban teacher residency program in Newark as they reinvent math and science teaching and teacher education through the lens of inquiry. Each chapter includes narratives from multiple perspectives as well as tools we have used within the program to support and build change, providing readers with both real cases of how an urban teacher residency can impact school systems, and concrete tools and examples to help the reader understand and replicate aspects of the process. Capturing both the successes but also the tensions and challenges, we offer a kaleidoscopic view of the rich, complex, and multi-layered ways in which multiple stakeholders work together to make enduring educational change in urban schools. Our third space NMUTR has been a fragile utopian enterprise, one that has relied on a shared commitment of all involved, and a deep sense of hope that working collaboratively has the potential, even if not perfect, to make a difference.
Acknowledgements -- A Year in the Life of a Third Space Urban Teacher Residency -- Partnership: Origins of an Urban Teacher Residency -- Constructing and Negotiating a Residency Admissions Program in the Third Space -- Teaching for Social Justice through Funds of Knowledge in the Third Space -- The Missing Voice: Using Action Research to Bring Students into Third Space Preservice Education -- Preparing Residents to Teach English Language Learners in the Third Space -- Articulating the Intimate Knowledge of Teaching: Mentors and Faculty Design Protocols to Explore Video Artifacts of Teaching -- Science Pedagogical Content Knowledge Development in an Urban Teacher Residency -- Beyond School Walls: Engaging in Curriculum, Community, and the Complex World -- Inquiry and Induction in the Third Space -- Fostering Socially Just Teacher Leadership for Change in Urban Schools -- Epilogue: Ripple Effects and Reinvention in the Third Space -- Afterword.
Keywords: Education; Education; Education, general; Electronic books